2015
DOI: 10.1111/jcmm.12683
|View full text |Cite
|
Sign up to set email alerts
|

β cell membrane remodelling and procoagulant events occur in inflammation‐driven insulin impairment: a GLP‐1 receptor dependent and independent control

Abstract: Inflammation and hyperglycaemia are associated with a prothrombotic state. Cell‐derived microparticles (MPs) are the conveyors of active procoagulant tissue factor (TF) and circulate at high concentration in diabetic patients. Liraglutide, a glucagon‐like peptide (GLP)‐1 analogue, is known to promote insulin secretion and β‐cell preservation. In this in vitro study, we examined the link between insulin impairment, procoagulant activity and plasma membrane remodelling, under inflammatory conditions. Rin‐m5f β‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Rin‐m5f rat insulin‐secreting cells were chosen as an adequate model for the study of the β cell response to prolonged oxidative stress and hyperglycaemia. Indeed, although not responsive to a short metabolic raise by glucose stimulation, Rin‐m5f develop apoptosis after prolonged exposure to H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Rin‐m5f rat insulin‐secreting cells were chosen as an adequate model for the study of the β cell response to prolonged oxidative stress and hyperglycaemia. Indeed, although not responsive to a short metabolic raise by glucose stimulation, Rin‐m5f develop apoptosis after prolonged exposure to H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were incubated with serum-free media for 24 h prior to each experiment and seeded at 1 × 10 6 cells/dish in 100 mm culture dishes for western blotting and 3 × 10 4 cells/well in 24-well-culture plates for immunofluorescence. To study the role of GLP-1R in microglial inflammation, BV-2 cells were preincubated with the selective GLP-1R agonist liraglutide (100 nM, Selleck, TX, USA) and the antagonist exendin(9-39) (200 nM, MCE, USA) for 24 h, followed by LPS (1 µg/ml, Sigma-Aldrich, MO, USA) stimulation for 24 h. The doses of these drugs used with cells were based on previous data [34][35][36].…”
Section: Body Weight and Blood Glucose Testmentioning
confidence: 99%
“…GLP-1 stimulates PKA-dependent phosphorylation of synaptotagmin-7, a crucial Ca 2+ sensor affiliated with SNARE-mediated exocytosis, thereby boosting glucose- and Ca 2+ -stimulated insulin secretion [ 123 ]. Liraglutide, a GLP-1 analog, was reported to modulate plasma membrane-raft clustering in RIN-m5f β-cells, possibly impacting functionality of raft-embedded SNARE protein isoforms STX1, SNAP25, and VAMP2 [ 124 ]. Indeed, earlier studies showed GLP-1 to enhance insulin secretion via mobilizing and docking an increased number of ISGs at the plasma membrane and accelerating sequential ISG—ISG fusions [ 118 ].…”
Section: Exocytosis Proteins and β-Cell Functionmentioning
confidence: 99%